2006
DOI: 10.1002/pi.2054
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced birefringence in blends of a polyurethane bearing azobenzene moieties and a poly(amide–imide)

Abstract: A polyurethane (MDI-DR19Cl) bearing azobenzene moieties was prepared by condensation of 4,4diphenylmethylenediisocyanate and an azobenzene compound, 2-chloro-4-nitro-4 -[bis-(2-hydroxyethyl)]amineazobenzene (DR19Cl). Blends of MDI-DR19Cl and a poly(amide-imide) were prepared and characterized by UV-visible and Fourier transform infrared spectroscopy and by DSC. The purpose of using the blends was to overcome the lack of stability of cast films of pure MDI-DR19Cl, which tend to crack on storage under ambient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%